VOLUME 6. NUM 2. SUPPLEMENT. ABSTRACT. RUSSIAN CONGRESS 2016 (Ozone Therapy Global Journal, 2016)
X RUSSIAN SCIENTIFIC CONFERENCE IN OZONE-THERAPYV INTERNATIONAL JOINT CONFERENCE RUSSIAN-IMEOFOzone:  active forms of oxygen, nitrogen oxides and high-intensity. Its physical factors in biology and medicine.Nizhny Novgorod, September 14-16, 2016